L’insertion des habitants des favelas de Rio de Janeiro dans la ville : le cas des pratiques de consommation et de loisirs - Michael Chetry (Confins)
This paper presents the results of a research on the spatial practices of the inhabitants of favelas in Rio de Janeiro developed in a framework of a PhD. This research shows that the inhabitants of favelas have a good experience of the urban space and are willing to access the various resources available in the city, which is unfortunately limited by their low mobility. But overall, the inhabitants of favelas are increasingly included into the urban space and living in a favela does not imply having a different lifestyle from other city residents. Instead, it incorporates the norms and values of the dominant society and its main places and symbols.